1997
DOI: 10.1086/593812
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion-Transmitted Babesiosis in Washington State: First Reported Case Caused by a WA1-Type Parasite

Abstract: Most cases of babesiosis reported in the United States have been tickborne and caused by Babesia microti, the etiologic agent of all previously described transfusion-transmitted cases. A 76-year-old man with the first recognized case of transfusion-transmitted infection with the recently identified WA1-type Babesia parasite is described. The subject received multiple blood transfusions in 1994. Indirect immunofluorescent antibody testing of serum from 57 blood donors implicated a 34-year-old man (WA1 titer, 1:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(85 citation statements)
references
References 12 publications
4
80
0
1
Order By: Relevance
“…Several cases of transfusion-associated babesiosis have been described, mainly in the United States (to the authors' knowledge, none were from Europe) (167).…”
Section: Other Parasitic Infectionsmentioning
confidence: 92%
“…Several cases of transfusion-associated babesiosis have been described, mainly in the United States (to the authors' knowledge, none were from Europe) (167).…”
Section: Other Parasitic Infectionsmentioning
confidence: 92%
“…Later reports also described infections with WA1-type organisms, which were acquired via blood transfusion in patients from Washington State (267) (isolates WA2 and WA3) and California (327) (isolates CA5 and CA6). Herwaldt et al (267) PCR amplified sections of the SSU rDNAs from WA2 and WA3, which were found to be identical to each other and to WA1. Kjemtrup , and CA6).…”
Section: Babesia Sppmentioning
confidence: 99%
“…Gerber et al (11), in a study of patients having undergone cardiothoracic surgery with multiple blood transfusions, noted that the risk of acquiring babesiosis from packed erythrocytes was 0.17%, making it a potential but minor threat to the blood supply. Nevertheless, transmissions are now well-documented in the literature (7,11,17,28,47,55).…”
Section: Babesia and The Blood Supplymentioning
confidence: 99%
“…Like the malaria agent, the parasite attacks and damages host erythrocytes. The disease is transmitted to humans by infected ticks, a route shared with the agents of spotted fever, borreliosis, and ehrlichiosis; human-to-human transmission does not occur with the exception of transfusion-mediated spread (7,17). Babesia is placed in the same taxonomic group-the Piroplasmida-as another blood parasite, Theileria.…”
Section: Introductionmentioning
confidence: 99%